ANALISIS PERTIMBANGAN MAJELIS HAKIM ATAS PENGADUAN ATAU LAPORAN PALSU (Studi Kasus Putusan Nomor : 10/Pid.B/2023/PN.Tul) - Monica Atma Negara; Margo Hadi Pura (Universitas Wiralodra, 2025)
ABSTRACT This research aims to identify the elements that constitute a false report and analyze how the judges consider cases of false complaints. Through a normative legal approach, this study found that false reports are characterized by elements such as